Developing functional musculoskeletal tissues through hypoxia and lysyl oxidase-induced collagen cross-linking - Makris, Eleftherios A. (Proc Natl Acad Sci U S A, 2014)
The inability to recapitulate native tissue biomechanics, especially tensile properties, hinders progress in regenerative medicine. To address this problem, strategies have focused on enhancing collagen production. However, manipulating collagen cross-links, ubiquitous throughout all tissues and conferring mechanical integrity, has been underinvestigated. A series of studies examined the effects of lysyl oxidase (LOX), the enzyme responsible for the formation of collagen cross-links. Hypoxia-induced endogenous LOX was applied in multiple musculoskeletal tissues (i.e., cartilage, meniscus, tendons, ligaments). Results of these studies showed that both native and engineered tissues are enhanced by invoking a mechanism of hypoxia-induced pyridinoline (PYR) cross-links via intermediaries like LOX. Hypoxia was shown to enhance PYR cross-linking 1.4- to 6.4-fold and, concomitantly, to increase the tensile properties of collagen-rich tissues 1.3- to 2.2-fold. Direct administration of exogenous LOX was applied in native cartilage and neocartilage generated using a scaffold-free, self-assembling process of primary chondrocytes. Exogenous LOX was found to enhance native tissue tensile properties 1.9-fold. LOX concentration- and time-dependent increases in PYR content (∼16-fold compared with controls) and tensile properties (approximately fivefold compared with controls) of neocartilage were also detected, resulting in properties on par with native tissue. Finally, in vivo subcutaneous implantation of LOX-treated neocartilage in nude mice promoted further maturation of the neotissue, enhancing tensile and PYR content approximately threefold and 14-fold, respectively, compared with in vitro controls. Collectively, these results provide the first report, to our knowledge, of endogenous (hypoxia-induced) and exogenous LOX applications for promoting collagen cross-linking and improving the tensile properties of a spectrum of native and engineered tissues both in vitro and in vivo.